2019
DOI: 10.1016/j.jpba.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the suitability of ionic liquid-based liquid-liquid microextractions for blood protein removal

Abstract: The analysis of biological samples, such as whole blood, comes with several sample preparation challenges. Biological matrices often contain a variety of endogenous components that can interfere with the determination of xenobiotics. Especially blood plasma proteins (e.g. serum albumin) are known to interfere with electrospray ionization and result in analyte ion suppression. Sample preparation techniques should guarantee adequate removal of these biomolecules. The current study aims to determine to which exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The pretreated samples were then investigated for the clearance of proteins and lipids according to the method reported previously (De Boeck et al, 2019; Visnovitz et al, 2019). The results showed that the MTBE + ACN method could significantly reduce the lipids of the sample compared with ACN alone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pretreated samples were then investigated for the clearance of proteins and lipids according to the method reported previously (De Boeck et al, 2019; Visnovitz et al, 2019). The results showed that the MTBE + ACN method could significantly reduce the lipids of the sample compared with ACN alone.…”
Section: Resultsmentioning
confidence: 99%
“…The protein has a strong absorption at 280 nm. Protein absorption has been reported to be proportional to the concentration (De Boeck et al, 2019). The sulfo-phospho-vanillin lipids assay was introduced to determine the content of lipids in the pretreated samples (Visnovitz et al, 2019).…”
Section: Measurement Of Proteins and Lipidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently common pretreatments are solid phase extraction (SPE), liquid liquid extraction (LLE) and protein precipitation (PP). [32][33][34][35] SPE bases on the difference in partition coefficient between the solid phase and the liquid phase of the target to separate the target from urine sample. And it requires long-time extraction and complex multi-step process.…”
Section: Introductionmentioning
confidence: 99%